Timing in Speech : A Review of Literature - SR, Savithri (Journal of All India Institute of Speech and Hearing)
The paper reviews the literature on durational models, role of duration in speech perception and factors affecting the duration of speech sounds. In the course of discussion, several areas warranting further research have been identified. Further, the paper briefly dwells on the notions of ancient Indian scholars on durational models.